1993
DOI: 10.1161/01.str.24.9.1322
|View full text |Cite
|
Sign up to set email alerts
|

Value of single-photon emission-computed tomography in acute stroke therapeutic trials.

Abstract: Background and Purpose: New therapeutic interventions for acute ischemic stroke are aimed at improving cerebral blood flow in the first 3 to 6 hours after symptom onset. Single-photon emissioncomputed tomography (SPECT) performed in the setting of clinical therapeutic trials may give us a better understanding of the physiological response to new forms of treatment and could impact acute management decisions.Methods: We prospectively studied 15 patients with hemispheric ischemic stroke with SPECT within 6 hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(40 citation statements)
references
References 20 publications
7
33
0
Order By: Relevance
“…The SPECT graded scale in our semiquantitative SPECT analysis is a combination of the size and extent of ischemia and had a high sensitivity and specificity to predict malignant MCA infarction/death. This confirms the results of Hanson et al, 29 who also found a strong association between the severity of ischemia (SPECT graded scale) on the initial SPECT scan and poor long-term outcome (Barthel Index), albeit among just 15 patients examined within 6 hours.…”
Section: Berrouschot Et Al December 1998supporting
confidence: 90%
See 2 more Smart Citations
“…The SPECT graded scale in our semiquantitative SPECT analysis is a combination of the size and extent of ischemia and had a high sensitivity and specificity to predict malignant MCA infarction/death. This confirms the results of Hanson et al, 29 who also found a strong association between the severity of ischemia (SPECT graded scale) on the initial SPECT scan and poor long-term outcome (Barthel Index), albeit among just 15 patients examined within 6 hours.…”
Section: Berrouschot Et Al December 1998supporting
confidence: 90%
“…A few SPECT studies performed within 6 hours of stroke onset relied on small patient numbers and did not address the prediction of death after stroke. 29,[33][34][35][36] These studies exclusively used the tracer 99m Tc-HMPAO, which assesses cerebral blood flow. By contrast, the tracer 99m Tc-ethyl-cysteinatedimer (ECD) reflects not only perfusion but also the metabolic status of the brain tissue and may be more specific for revealing the degree of irreversible brain lesions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It additionally emphasizes the importance of outcome SPECT studies in retrospectively distinguishing the nutritional and nonnutritional components of early reperfusion. Previously published studies by our group 18,19 and others 32,33 have shown that acute reperfusion after therapeutic intervention does not necessarily correlate with clinical gains. By supplementing early studies with studies in the chronic phase, we have shown that the enhanced early reperfusion after nimodipine did not correlate with clinical improvement because it was transient and occurred in nonviable tissue.…”
Section: Discussionmentioning
confidence: 92%
“…The mechanism(s) underlying cerebral ischemic symptoms is thought to be hemodynamic at first as a result of significant stenosis or occlusion of the carotid artery involved by dissection extending to the A1 segment. 6,22 . In our case, immediate STA-MCA anastomosis was completed within the therapeutic time window [23][24][25] and narrowly escaped fatal deficits developed. There has not been established authentic strategies for the spontaneous dissection of the CS ICA to prevent complete stroke yet.…”
Section: Case Reportmentioning
confidence: 99%